Upscaling Effects of Soil Improvement by Microbially Induced Calcite Precipitation by Surface Percolation - Cheng, Liang; Cord-Ruwisch, R. (Taylor & Francis, 2014)
This study has contributed to the technology of soil stabilization via biocementation based on microbially induced calcite precipitation. The newly described method of in situ soil stabilization by surface percolation to dry soil under free draining environment is tested for its up-scaling potential. Then, 2-m columns of one-dimensional trials indicated that repeated treatments of fine sand (<0.3 mm) could lead to clogging closed at the injection end, resulting in limited cementation depth of less than 1 m. This clogging problem was not observed in 2 m coarse (>0.5 mm) sand columns, allowing strength varying between 850 to 2067 kPa along the entire 2 m depth. Three-dimensional fine sand cementation trials indicated that relatively homogenous cementation in the horizontal direction could be achieved with 80% of cemented sand cementing to a strength between 2 to 2.5 MPa and to a depth of 20 cm. A simple mathematical model elucidated that the cementation depth was dependent on the infiltration rate of the cementation solution and the in-situ urease activity. The model also correctly predicted that repeated treatments would enhance clogging close to the injection point. Both experimental and simulated results suggested that the surface percolation technology was more applicable for coarse sand.